A governança corporativa como determinante dos juros sobre o capital próprio e dos dividendos - Hauschildt, Rogerio (2023)
The investor's remuneration combined with the tax benefit is a topic of academic debate, making the issue of dividend distribution and/or payment of Interest on Equity (JSCP) crucial for both the company and investors. This research is related to the theme of JSCP and dividend distribution beyond the traditional tax perspective, being analyzed from the perspective of Corporate Governance. The general objective of the study is to analyze the impact of corporate governance on the payment of JSCP and dividends in publicly traded companies listed on the Brazilian stock exchange (B3). The study sample consists of 10,579 observations, unbalanced and with gaps, from companies with shares listed on B3 for the period from 2013 to 2022. The main statistical technique used is regression with panel data with Ordinary Least Squares (OLS) estimation. The results indicate that governance proxies have a differential impact on the distributions of Dividends and JSCP. Considering the signal divergence, it is pointed out that an increase in CEO remuneration leads to an increase in the distribution of JSCP, and a decrease in the distribution of Dividends. The size of the board presented parity of signs for both models. Along the same lines, the variable Council Independence presented parity of signs for both models. The research contributes to expanding the debate on the distribution of dividends and JSCP beyond the traditional tax perspective, offering a new perspective where it analyzes governance proxies as determinants of the distribution of dividends and JSCP, highlighting the role of corporate governance in financial decision-making. As a practical contribution, it emphasizes the importance of considering governance structures in financial decision-making and provides valuable information for researchers, companies, investors, and policymakers.